Comparison of lung diffusing capacity in young elite athletes and their counterparts - Lazoic, B.; Zlatkovic-Svenda, M.; Grbovic, J.; Milenkovic, B.; Sipetic-Grujicic, S.; Kopitovic, I.; Zugic, V. (Pulmonology, 2018)
Background: The influence of exercise on the pulmonary function is controverse, some studies have reported no sports influence, while the others have found positive correlation. Aim: To evaluate and compare the sports influence on pulmonary function: spirometry (VC, FVC, FEV1, FEV1/FVC), lung diffusing capacity (DLCO) and coefficient of the CO gas transfer (KCO) in two elite athletes groups and healthy sedentary controls. Method: Equally divided into aerobic and anaerobic group, 60 elite athletes were recruited, as well as 43 age-matched, healthy sedentary controls. All of the participants performed basic anthropometric measurements, spirometry, DLCO and KCO at rest. Kruskal-Wallis one way ANOVA test was used to determine differences between groups; Mann-Whitney U test was used for inter-groups differences and Pearson coefficient for pulmonary variables and anthropometric parameters correlation. Statistical analyses were performed using the SPSS computer statistic program, version 20. Results: No differences were found in pulmonary characteristics (spirometric function values, DLCO and KCO) in athletes and non-athletes at rest, as well as between aerobics and anaerobics. There were no correlations between the anthropometric parameters and the investigated respiratory function tests. DLCO (%) correlated positively with height in athletes playing anaerobic type of sport (karate and taekwondo) (p = 0.036; r = 0.544), and negatively in sedentary control group (p = 0.030; r = -0.560). Regarding KCO, no differences were found. Conclusion: Spirometry indices and DLCO are not influenced either by aerobic or anaerobic training type, so benefits of sports on pulmonary indices or DLCO was not confirmed.